Analysis of the civil service control (admission) model of the Republic of Azerbaijan with models related to the application of the model in international practice - Mammadov, Toghrul; Salahli, Asia; Hasanli, Sadig (My University, 2022)
Radical reforms have been carried out in the area of admission to the civil service for many years and significant progress has been made in this area. This project aims at studying the existing model of the admission to the civil service in the country, as well as to study international experience in this field and, accordingly, to make relevant proposals in accordance with international experience in this sphere. The project revealed that there are difficulties in the field of recruitment to management positions in the field of civil service, testing of candidates' professional (specialty knowledge) knowledge, as well as the payment system used in the examination process. In this regard, in order to overcome the above mentioned difficulties, the project proposes to apply a special system to check the managerial skills of persons appointed to managerial positions, to apply appropriate procedures to check the qualifications of candidates and to apply benefits to special categories of applicants. All of the above solutions were evaluated according to the criteria of efficiency, effectiveness, equity (fairness), feasibility (implementability) and flexibility. Second data, expert opinions in the relevant field, as well as information on survey outcomes were used in the development of the project. As a result of the analysis and assesment it was determined that in order to improve the admission procedures in the civil service related to the mentioned problems, civil service recruitment process (testing of knowledge and skills) should be improved, while certain discounts should be applied to the payment system for participation in examinations.
Keywords: Civil service control.; Civil service control -- Azerbaijan.; International practice.; Public and International Affairs